MEMBANGUN KUALITAS PELAYANAN PUBLIK MELALUI PENINGKATAN ETOS KERJA PEGAWAI - Carmia Diahloka; Achmad Bardjan Shaleh (REFORMASI, 2013)
Many government employees at certain level must put passion of work for serving public needs as a foundation of their motivation and dedication when choosing a career in governmental area. An understanding about government mission in maintaining order and preserving a justice in direct move makes public service to be the primary function. The purpose of this research is to find out how to build a qualified public service through enhancing work ethic / ethos of their employees. Type of the research is descriptive qualitative and tries to explosure more about work ethics and finding data of the employees at Dinas Pertanian, Perikanan dan Peternakan at Sanggau Regency. Primary data collecting methods is questioner instrument. The research result indicates that through a good work ethics/work ethos become alternative way to enhancing public service which consist of manner, attitude and responsibility of Dinas Pertanian, Perikanan, dan Peternakan employees in their duties.